Neuroprotective effects of thymoquinone-rich fraction and thymoquinone nanoemulsions in sporadic alzheimer’s disease rat model - Ismail, Norsharina (2019)
Increasing life expectancy has produced a dramatic rise in age-associated diseases including Alzheimer's disease (AD). Oxidative stress is one of the most vital risk factor which can potentially lead to the AD pathogenesis such as amyloid-β (Aβ) deposits. The existing treatment of AD only relies on the two types of drug, namely the acetylcholinesterase inhibitors and N-methyl-D-aspartate receptor antagonist. Due to the limitations of these existing drugs, new treatments and therapeutic strategies on AD management are emerging. Despite of the neuropharmacological attributes of Nigella sativa (black cumin seeds) and its active constituent, thymoquinone (TQ), limited records are available in relation to AD researches. Thus, the present study was conducted to investigate the neuroprotective effects of thymoquinone-rich fraction (TQRF) and TQ in sporadic AD models, and their underlying mechanistic actions. In vitro efficacy of TQRF and TQ was investigated against hydrogen peroxide (H2O2)- induced oxidative stress in human neuroblastoma SH-SY5Y cells through cell viability assay, reactive oxygen species (ROS) assay, morphological observation, and gene expression analysis. As a result, TQRF and TQ protected the cells against H2O2 toxicity by preserving the mitochondrial metabolic enzymes, reducing intracellular ROS levels, preserving morphology of cells and modulating the expression of antioxidants (SOD1, SOD2 and catalase), and apoptotic signaling (p53, AKT1, ERK1/2, p38 MAPK, JNK and NF-ĸβ) genes (p < 0.05). In vivo efficacy of TQRF and TQ was evaluated using a high fat-cholesterol diet (HFCD) model of sporadic AD. The oral bioavailability of poor water soluble TQRF and TQ were improved through nanotechnology approach in the form of nanoemulsion (NE), namely as TQRFNE and TQNE, respectively. The TQRF and TQ conventional emulsions (CE), named as TQRFCE and TQCE, respectively were studied for comparison. Statin (Simvastatin) and non-statin (Probucol) cholesterol-lowering agents, and AD drug (Donepezil) were served as control drugs. The Sprague Dawley rats were fed with HFCD for 6 months, and treated with the intervention groups daily for the last 3 months. The Morris Water Maze learning and memory test, and biochemical analyses (lipid profile, lipid peroxidation, antioxidant and soluble amyloid-β (Aβ) levels were measured. The neuroprotective mechanistic actions of the intervention groups were determined through gene and protein expression levels. The HFCD-fed rats exhibited hypercholesterolaemia, accompanied by memory deficit, increment of lipid peroxidation and soluble Aβ levels, decrement of total antioxidant status and downregulation of antioxidants genes expression levels (p < 0.05). Nevertheless, TQRFNE diminished those detrimental effects of HFCD through the modulation of Aβ generation (APP, BACE1, PSEN1 and PSEN2), Aβ degradation (IDE), Aβ transportation (LRP1 and RAGE), neuroinflammation genes (CRP, NOS1, TNF-α and PPARγ) (p < 0.05), and lessen the hippocampus injury. In conclusion, TQRF has potential to be developed as a nutraceutical product for the management of neurodegenerative diseases owing to oxidative stress including AD.